2015
DOI: 10.3945/ajcn.114.105205
|View full text |Cite|
|
Sign up to set email alerts
|

Cesarean delivery and metabolic risk factors in young adults: a Brazilian birth cohort study

Abstract: In our sample of Brazilian adults, CD was associated with higher BMI but not with other metabolic risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 62 publications
2
22
0
1
Order By: Relevance
“…Our findings on the association of delivery mode with childhood OWOB are consistent with a growing body of literature 9,13,15 . A meta-analysis that found Cesarean delivery increases odds of childhood overweight or obesity by approximately 30% 9 —a magnitude of association comparable to our study.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings on the association of delivery mode with childhood OWOB are consistent with a growing body of literature 9,13,15 . A meta-analysis that found Cesarean delivery increases odds of childhood overweight or obesity by approximately 30% 9 —a magnitude of association comparable to our study.…”
Section: Discussionsupporting
confidence: 92%
“…(2013) and Bernardi et al . (2015) reported increase in fat accumulation due to delivery by CS: measured by either waist-hip ratio (IRR 1.45, 95% CI 1.18-1.79) [23] or BMI (β coefficient 0.12, 95% CI 0.01-0.03) [24]. More recently, Yuan et al (2016) and Barros et al (2017) reported increased risks of obesity in CS-delivered YAs (RR 1.15, 95% CI 1.06-1.26, n= 8 486; β coefficient 0.15, 95% CI 0.08-0.23, n= 1 794, respectively) in Boston (USA) and Pelotas (Brazil) [19,26].…”
Section: Discussionmentioning
confidence: 99%
“…Children born via cesarean compared to those born vaginally are more likely to develop immune-related disorders like asthma/allergies (Black, Bhattacharya, Philip, Norman, & McLernon, 2016; Kristensen & Henriksen, 2016), inflammatory bowel disease (Kristensen & Henriksen, 2016), and obesity (Bernardi et al, 2015; Li, Zhou, & Liu, 2013; Mueller et al, 2015). Although not all of these associations are shown consistently in all studies (Bernstein et al, 2016; Black et al, 2016), these findings have led some researchers to speculate that alterations in microbiome seeding of newborns following cesarean birth may play some role in these associations between chronic disease and route of birth (Dominguez-Bello et al, 2016; Goedert, Hua, Yu, & Shi, 2014).…”
Section: Implications Of Route Of Birthmentioning
confidence: 99%